2018
DOI: 10.1186/s12885-018-4828-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive factors for angiosarcoma patients receiving paclitaxel once weekly plus or minus bevacizumab: an ancillary study derived from a randomized clinical trial

Abstract: BackgroundWe report here a correlation analysis conducted along with a phase II trial assessing bevacizumab in combination with weekly paclitaxel.MethodsCirculating pro/anti-angiogenic factors were assessed on day 1 (D1) and day 8 (D8). The prognostic value for progression-free survival (PFS) was evaluated using a Cox model with biomarkers as continuous variables.ResultsAmong the 51 patients enrolled and treated in this trial, biomarker analysis was performed for 42: 18 in Arm A (single-agent) and 24 in Arm B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In addition to IL‐23p19, PAI‐1 also increased the mRNA expressions of VEGF‐C, CXCL5 and CCL20 on ISO‐HAS‐B angiosarcoma cells. Notably, angiosarcomas overexpress multiple VEGF receptors (VEGFRs) including VEGFR‐3, 33 and increased VEGF‐C expression correlates with cell proliferation in CAS 34 . Another report suggested that baseline VEGF‐C was associated with a poor prognosis of de novo angiosarcoma 35 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IL‐23p19, PAI‐1 also increased the mRNA expressions of VEGF‐C, CXCL5 and CCL20 on ISO‐HAS‐B angiosarcoma cells. Notably, angiosarcomas overexpress multiple VEGF receptors (VEGFRs) including VEGFR‐3, 33 and increased VEGF‐C expression correlates with cell proliferation in CAS 34 . Another report suggested that baseline VEGF‐C was associated with a poor prognosis of de novo angiosarcoma 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The response rate to combination therapy was not only lower (29% vs 46%), these patients also experienced more frequent severe toxicities 31 . The evaluation of circulating pro/anti-angiogenic factors did not identify any subgroup that benefited from the addition of bevacizumab 41 . More recently, TRC105, an antibody against an essential angiogenic receptor known as endoglin, did not demonstrate significant activity when combined with pazopanib, a tyrosine kinase inhibitor with anti-angiogenic activity 42 .…”
Section: Discussionmentioning
confidence: 95%
“…However, no significant difference in PFS between treatment groups is reported. Unfortunately, even in combination with target agents such as bevacizumab response rates remained disappointing ( 92), (93)(94)(95).…”
Section: Conflict Of Interestsmentioning
confidence: 99%